2021
DOI: 10.3892/etm.2021.9674
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian endometriosis, a precursor of ovarian cancer: Histological aspects, gene expression and microRNA alterations (Review)

Abstract: Ovarian endometriosis is a frequent chronic gynecological disease with an uncertain evolution regarding its progression or association with ovarian malignant lesions. The present review summarized the histological aspects, gene expression and microRNA (miRNA/miR) alterations associated with ovarian endometriosis and cancer and their possible interaction. The endometriosis-ovarian cancer interaction has been proposed by certain researchers as a single entity. Histological results indicated that endometriosis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 77 publications
0
33
0
6
Order By: Relevance
“…Histopathologically, the malignant transformation is recognized as cytologic atypia and architectural proliferation [ 10 ]. Cytologic atypia is defined as the transition from benign EM to carcinoma and is classified as moderate (simple hyperplasia or cellular atypia) or severe (complex hyperplasia or cellular atypia that is more evident) [ 11 ]. Concerning cellular proliferation, complex hyperplasia is translated into glandular proliferation and reduced stroma, which can evolve towards ovarian cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Histopathologically, the malignant transformation is recognized as cytologic atypia and architectural proliferation [ 10 ]. Cytologic atypia is defined as the transition from benign EM to carcinoma and is classified as moderate (simple hyperplasia or cellular atypia) or severe (complex hyperplasia or cellular atypia that is more evident) [ 11 ]. Concerning cellular proliferation, complex hyperplasia is translated into glandular proliferation and reduced stroma, which can evolve towards ovarian cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytologic atypia is defined as the transition from benign EM to carcinoma and is classified as moderate (simple hyperplasia or cellular atypia) or severe (complex hyperplasia or cellular atypia that is more evident) [ 11 ]. Concerning cellular proliferation, complex hyperplasia is translated into glandular proliferation and reduced stroma, which can evolve towards ovarian cancer [ 11 ]. As mentioned above, endometrioid carcinoma or clear cell carcinoma are the most prevalent types, and their gross appearance consists of the typical histology of each type of malignancy including cribiform, glandular or solid architecture and papillary, solid or tubulocystic architecture for each cancer type, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that endometriosis is one of the risk factors for ovarian cancer [ 8 ], and a proportion of ovarian cancers have been shown to originate from 0.5 to 1% of cases of ovarian endometriosis [ 9 , 10 ]. Ovarian endometriosis may present a risk for ovarian malignant lesions according to gene expression and miRNA alterations [ 11 , 12 ], and is always managed with the prevention of carcinogenesis [ 13 ]. Immunity and inflammation are thought to be strongly associated with carcinogenicity [ 14 , 15 ]; however, no studies have shown how long ovarian cancer takes to develop from ovarian endometriosis.…”
Section: Introductionmentioning
confidence: 99%